L’ipotesi di Parmenide in Parm. 137b1-4: cosmologia, enologia o ontologia? - Francesco Fronterotta (Études Platoniciennes, 2019)
In Plato’s Parmenides (135c8-d5), Parmenides suggests Socrates to practice a dialectical exercise before the search for truth: this exercise consists in verifying the logical consistence of the consequences of a certain hypothesis and of its reversal, as regards the object of the hypothesis and its opposite. In a very short passage (137b1-4)), Parmenides states that his analysis will be dedicated to the one itself and that it will start from his philosophical thesis. But what’s the object of Pamenides’ hypothesis? The one, as the text seems to mean, or the principle of the unity of the all, which is Parmenides’ fundamental thesis in the dialogue named after him? This paper intends to clarify the content of Parmenides’ hypothesis.